Understanding Chinese Nursing Education and Practice for Developing International Nursing Partnerships. (July 2020) - He, Qilian; Fu, Yanfen; Su, Yunpeng; Luan, Yuquan
Introduction: Modern nursing was introduced into China by Western missionaries in the 19th century; since then, significant changes continued to occur, which provides beneficial areas of international collaboration based on trends in globalization.Methods and Materials: The description was developed through reviews of published literature, policy documents that inform Chinese nursing practice, education, and the firsthand working experiences between American and Chinese nurses and faculty.Results: 82 articles and 13 governmental documents were included. Chinese nursing has undergone significant changes in the organization, quality assessment, and roles requirements in education and practice. International collaboration areas include addressing the severe faculty shortage, maternal child care, elderly care, quality assessment, and educational programs evaluation.Discussion: Informative knowledge of changing Chinese nursing education and practices in the new millennium, the potential areas, and guides for international nursing collaboration would be meaningful to internationally involved faculty and nurses in China and America.